Hubungan antara Growth Mindset dan Grit Akademik pada Mahasiswa Bekerja - Aisya Azlina Mayshita; Fadjri Kirana Anggarani; Laelatus Syifa Sari Agustina (Jurnal Ilmiah Psikologi Candrajiwa, 2023)
Abstract. Academic grit is a behavior to maintain perseverance and enthusiasm in achieving long-term goals. To increase grit, growth mindset is needed. Individuals with a growth mindset believe that their abilities can be continuously improved with certain effort and hard work. This study aims to determine the relationship between growth mindset and academic grit in working college students of UNS with 86 students used as sample which determined by incidental sampling technique. The measurement tools used are the growth mindset scale (α=0.913) and the academic grit scale (α=0.869). The data was processed using a simple linear regression analysis technique and showed a positive and significant relationship between the two variables with Fcount>Ftable (89.626 > 3.96) and R is 0.718 (strong correlation). R2 is 0.516 which can be interpreted that the growth mindset variable in this study has 51,6% effectively contributed to the academic grit variable.Abstrak. Grit akademik merupakan perilaku untuk mempertahankan ketekunan dan semangat dalam mencapai tujuan jangka panjang. Grit dapat ditingkatkan dengan growth mindset. Individu dengan growth mindset meyakini bahwa kemampuan seseorang dapat terus ditingkatkan dengan usaha dan kerja keras. Penelitian ini bertujuan untuk mengetahui hubungan antara growth mindset dan grit akademik pada mahasiswa UNS yang bekerja dengan sampel sebanyak 86 mahasiswa yang ditentukan melalui teknik incidental sampling. Alat ukur yang digunakan adalah skala growth mindset (α=0,913) dan skala grit akademik (α=0,869). Data diolah menggunakan teknik analisis regresi linear sederhana dan menunjukkan adanya hubungan positif antara kedua variabel dengan Fhitung>Ftabel (89,626 > 3,96) dan R sebesar 0,718 (korelasi kuat). R2 sebesar 0,516 dengan artian variabel growth mindset memiliki sumbangan efektif sebesar 51,6% terhadap variabel grit akademik.